2014
DOI: 10.3109/10903127.2014.983661
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Safe EMS Transport of Patients Infected with Ebola Virus

Abstract: The Nebraska Biocontainment Unit through the Nebraska Medical Center in Omaha, Nebraska, recently received patients with confirmed Ebola virus from West Africa. The Nebraska Biocontainment Unit and Omaha Fire Department's emergency medical services (EMS) coordinated patient transportation from airport to the high-level isolation unit. Transportation of these highly infectious patients capitalized on over 8 years of meticulous planning and rigorous infection control training to ensure the safety of transport pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Ground transport usually involves the use of an ambulance. It is recommended that the ambulance be draped with an impervious barrier or otherwise modified to decrease the possibility of contamination of the vehicle during transport [12,13]. Strict infection control practices should be followed during all phases of transport, including the use of appropriate PPE for both the patient and the healthcare workers, and separation of the driver compartment from the passenger compartment [14].…”
Section: Transportationmentioning
confidence: 99%
“…Ground transport usually involves the use of an ambulance. It is recommended that the ambulance be draped with an impervious barrier or otherwise modified to decrease the possibility of contamination of the vehicle during transport [12,13]. Strict infection control practices should be followed during all phases of transport, including the use of appropriate PPE for both the patient and the healthcare workers, and separation of the driver compartment from the passenger compartment [14].…”
Section: Transportationmentioning
confidence: 99%
“…If there is a problem like Finding lack of coordination within an organization or between the responsible agencies in transmission the patient, some joint meetings will be held to discuss and resolve potential failures and correct action guidelines and the results of these meetings will be communicated as a decision to all organizations [12,13,15,16].…”
Section: The Overall Assessment Of the Patient Transfer Processmentioning
confidence: 99%
“…Try to bring a clean stretcher with necessary equipment's for transmission the patient, close EMS ambulance and also in transferring the patients from ambulance to hospital we should use special track is covered with waterproof sheet. It is better emergency medical services' personnel don't interfere in the transferring the patient to his hospital room because the possibility of contamination due to the contamination of clothes and hands, but if they do, after getting off the ambulance the stretcher's wheels and the soles of shoes of procedures staff must be disinfected with sodium hypochlorite 10% [4,11,15,16].…”
Section: Clinical Care While In Transitmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocontainment hospitals, such as Emory University Hospital and Nebraska Medical Center, have received confirmed EVD patients with advanced notice. 1 However, the challenge for most health care systems is the identification and management of EVD cases presenting unidentified and unannounced. The larger U.S. health care community quickly found that it was unprepared for the screening, isolation, and treatment of patients with suspected or confirmed EVD.…”
mentioning
confidence: 99%